Peningkatan Kemampuan Manajerial Kepala Madrasah melalui Pendidikan dan Latihan bagi Kepala Madrasah Ibtidaiyah Wilayah Kepengawasan Samigaluh Kulonprogo - Abdul Hamid Tarwaca (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2018)
The head master is chairman of education has an important role in increasing the quality of education, closely between the quality of head master with various aspects of the life of the madrasa as a discipline, the cultural climate of the madrasa and declining the behavior of the students. In addition, the head master is responsible for managing education microcomputer which is directly related to the learning process in the madrasa. Total Quality Management (TQM) or Integrated Quality Management (MMT) as a way of changing the paradigm of madrasah ibtidaiyah in managerial which aims to improve the quality of education at madrasah. Application of the TQM concept in the management of education indicates that the institution is the service industry to serve customers who have needs and how to satisfy customers. Thus the success of the madrasah is the success of the head master in the exercise of leadership and the ability to manajerialnya. The managerial capacity of the head master through education and training is an alternative management of madrasah in conceptual and empirical proved to be able to improve the quality of the madrasa. The head master has a very important role in the improvement of character education, therefore the candidate head of the madrasa and it shall be a good teacher, in order to carry out its role and its function with no exception. The difference in the condition of madrasa affect managerial development and improvement of the head of the madrasa for improving the quality of education at madrasah.